Trinidad and Tobago : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Trinidad and Tobago is slowly recovering from a deep recession. The economy continued to contract but at a slower pace, underpinned by the strong recovery in gas production, while weak activity in construction, financial services, and trade, continued foreign exchange shortages, and slow pace of public investment dampened non-energy sector growth. Positive growth should return from 2018 as the recovery takes hold in both sectors. Good progress has been made in fiscal consolidation through spending cuts, but public debt continued to rise, approaching the government's soft target of 65 percent of GDP. Economic prospects are expected to improve over the medium term, but remain heavily dependent on the energy sector.